Association of body mass index trajectory and hypertension risk: A systematic review of cohort studies and network meta-analysis of 89,094 participants - Tan, Ling; Long, Lin-zi; Ma, Xiao-chang; Yang, Wen-wen; Liao, Fei-fei; Peng, Yu-xuan; Lu, Jie-ming; Shen, A-ling; An, Dong-qing; Qu, Hua; Fu, Chang-geng (Frontiers in Cardiovascular Medicine, 2023)
Background BMI trajectories are built from different trajectory modeling approaches to nonlinear time trends and nonlinear changes in BMI with age, which can provide information on the underlying patterns of BMI changes with age. The relationship between BMI trajectories and the risk of hypertension is still controversial. Methods The literature searches of PubMed, Embase, Cochrane, Scopus and Web of science databases were performed from inception to January 31, 2022. We classified BMI trajectories into the following five categories, “Stable high”, “Stable normal”, “Stable low”, “Fluctuated(sharp-increase)”, and “Fluctuated(elevated-decrease)”. The main outcome was the relative risks for the prevalence of hypertension in different BMI trajectories. Potential sources of heterogeneity were examined by meta-regression and subgroup analysis. Publication bias test and GRADE approach were also performed. Results Eighteen cohort studies including 89,094 participants were included. Compared with the “Stable normal” trajectory, the three trajectories of “Stable high”, “Fluctuated(sharp-increase)”, and “Fluctuated(elevated-decrease)” were all associated an increased risk of hypertension [RR (95%CI)]: [1.80(1.29~2.50), P<0.001; 1.53(1.27~1.83), P<0.001; 1.30 (1.24~1.37), P=0.001], while the “Stable low” trajectory was associated with a reduced risk of hypertension [0.83(0.79~0.83), P<0.001]. The BMI trajectory of “Stable high” (SUCRA=88.1%) had the highest probability of developing hypertension in the population. The certainty of evidence for direct comparisons of hypertension incidence between various BMI trajectories is generally very low. Conclusions Our findings suggest that the risks of developing hypertension across various BMI trajectories are different, with the “Stable high” trajectory most likely to cause hypertension.